Choice across 10 pharmacologic combination strategies for type 2 diabetes: a cost-effectiveness analysis - Shuyan Gu; Lizheng Shi; Hui Shao; Xiaoyong Wang; Xiaoqian Hu; Yuxuan Gu; Hengjin Dong (BMC Medicine, 2020)
Abstract Background Clinical guidelines recommend a stepped-escalation treatment strategy for type 2 diabetes (T2DM). Across multiple treatment strategies varying in efficacy and costs, no clinical or economic studies directly compared them. This study aims to estimate and compare the cost-effectiveness of 10 commonly used pharmacologic combination strategies for T2DM. Methods Based on Chinese guideline and practice, 10 three-stepwise add-on strategies were identified, which start with metformin, then switch to metformin plus one oral drug (i.e., sulfonylurea, thiazolidinedione, α-glucosidase inhibitor, glinide, or DPP-4 inhibitor) as second line, and finally switch to metformin plus one injection (i.e., insulin or GLP-1 receptor agonist) as third line. A cohort of 10,000 Chinese patients with newly diagnosed T2DM was established. From a healthcare system perspective, the Cardiff model was used to estimate the cost-effectiveness of the strategies, with clinical data sourced from a systematic review and indirect treatment comparison of 324 trials, costs from claims data of 1164 T2DM patients, and utilities from an EQ-5D study. Outcome measures include costs, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratios (ICERs), and net monetary benefits (NMBs). Results Over 40-year simulation, the costs accumulated for a patient ranged from $7661 with strategy 1 to $14,273 with strategy 10, while the QALY gains ranged from 13.965 with strategy 1 to 14.117 with strategy 8. Strategy 7 was dominant over seven strategies (strategies 2~6, 9~10) with higher QALYs but lower costs. Additionally, at a willingness-to-pay threshold of $30,787/QALY (i.e., 3 times GDP/capita for China), strategy 7 was cost-effective compared with strategy 1 (ICER of strategy 7 vs. 1, $3371/QALY) and strategy 8 (ICER of strategy 8 vs. 7, $132,790/QALY). Ranking the strategies by ICERs and NMBs, strategy 7 provided the best value for money when compared to all other strategies, followed by strategies 5, 9, 8, 1, 3, 6, 10, 2, and 4. Scenario analyses showed that patients insist on pharmacologic treatments increased their QALYs (0.456~0.653) at an acceptable range of cost increase (ICERs, $1450/QALY~$12,360/QALY) or even at cost saving compared with those not receive treatments. Conclusions This study provides evidence-based references for diabetes management. Our findings can be used to design the essential drug formulary, infer clinical practice, and help the decision-maker design reimbursement policy.